Prescrição automatizada de cadeiras de rodas de alto rendimento e de vida diária - Cardoso, Lucas de Souza (2020)
Currently, one of the main difficulties for tailor-made wheelchair industries is the unavailability of a prescriptive system that guarantees the reliable and accurate reproduction of the personal characteristics of the end-user. Conventional wheelchair prescription procedures are still inefficient and do not provide an ideal manufacturing condition. However, one of the essential challenges is in understanding how the wheelchair's ergo-anthropometric characteristics need to find a direct and objective correlation with the design of the wheelchair. Current systems require the presence of a qualified professional, or in most cases, it is done by filling out a prescriptive form sent online to the manufacturer. The purpose of this work was to develop a device with multiple adjustments to simulate the customized profile for a given wheelchair model that is based on the ergo-anthropometric characteristics of the wheelchair user. The constitution of this equipment considers the natures correlated to the personalization of the wheelchair, which are the person's anthropometric measurements and their ergonomic relationships with the use of the chair. An automated methodology for parameterizing high-performance wheelchairs and daily life was developed associated with the design and validation of this equipment. This system was developed for 09 different types of wheelchairs (serving 13 modalities) using innovative configurations and with automated modification of the structure with minimal interference from a designer. As a result, times for developing and manufacturing high-performance wheelchairs and daily life are drastically reduced. Another advantage of the entire prescription methodology is the possibility of pre-evaluating an adjustment to the equipment through 22 different types of adjustments and taking into account the physiological characteristics, the living environment and the lifestyle of the wheelchair user. The equipment and the new chairs were validated using finite element modeling. The complete prescription process has been validated for wheelchairs of daily life, indoor and outdoor tennis, table tennis, fencing, Paralympic bocce ball, target shooting or archery and cycling on sticks. The experimental tests provided the customization of these models for the evaluated athletes with their respective issued prescription forms. The results also provided some clarifications and changes in the psychomotor self-perception of these athletes during tests with different configurations, revealing essential aspects of their ergo-anthropometries. For the evaluated athletes, the methodology, as a whole, provides comfort, safety, physical fitness and ergonomic compatibility, in addition to the adequate modeling of wheelchairs. Among the evaluated athletes, the prescription methodology recommendation to third parties was unanimous. All models of wheelchairs for all evaluated athletes were automatically generated.